2013
DOI: 10.1163/18759866-08202003
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary patterns of asymmetric genitalia in the beetle tribe Cyclocephalini (Coleoptera: Scarabaeidae: Dynastinae)

Abstract: The evolution of asymmetric genitalia is a common and recurrent phenomenon in a wide variety of insect taxa. However, little is understood about the evolution of left-right asymmetry in reproductive structures. Since a better knowledge of it could have an important impact on the study of genital evolution, in the present study we investigate the phylogenetic and evolutionary patterns of asymmetric male genitalia in Cyclocephalini. We use a Procrustes distance based method for quantifying asymmetry. Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(104 citation statements)
references
References 23 publications
0
103
0
1
Order By: Relevance
“…In addition, very little is known about the relationships among cyclocephaline genera and species. Breeschoten et al (2013) presented a morphological phylogeny of cyclocephaline genera, but few details of the analysis were provided and the support for recovered relationships were not reported. Moore et al (2015) suggested that Mimeoma species were nested among a clade of Cyclocephala that included the type species of the genus, C. amazona .…”
Section: Evolution and Fossil Recordmentioning
confidence: 99%
“…In addition, very little is known about the relationships among cyclocephaline genera and species. Breeschoten et al (2013) presented a morphological phylogeny of cyclocephaline genera, but few details of the analysis were provided and the support for recovered relationships were not reported. Moore et al (2015) suggested that Mimeoma species were nested among a clade of Cyclocephala that included the type species of the genus, C. amazona .…”
Section: Evolution and Fossil Recordmentioning
confidence: 99%
“…Thanks to a wealth of information on genital morphology from the taxonomic literature [7], phylogenetic patterns are beginning to be elucidated [2,8,9]. However, a comprehensive understanding of the evolution of asymmetric genitalia has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…In the Coleoptera, male genital asymmetry is very common, while mating positions are mostly symmetric, male-above. Informal perusal of the coleopterological literature [2,3,13], as well as two studies of scarabaeoid beetles at tribe and genus level [8,9] show repeated evolution of asymmetry in several components of the male, and in some cases [14] also the female, genitalia. Moreover, cases of chiral reversal and antisymmetry are available for coleopteran taxa that are easily cultured and studied in the laboratory [3,4,15], making Coleoptera a suitable group for further study of the ultimate causes for genital chirality.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary, unpublished phylogeny of the superfamily Scarabaeoidea based on 28S and 18S molecular sequence data provided evidence that the cyclocephaline genera Dyscinetus Harold and Stenocrates Burmeister were more closely related to some Pentodontini (Dynastinae) (Eutheola Bates, Oxygrylius Casey and Tomarus Erichson) than to other cyclocephaline genera (Acrobolbia, Ancognatha, Aspidolea and Cyclocephala, in part), and demonstrated paraphyly of both tribes (Team Scarab, UNSM 2006). Second, a morphological analysis of the Cyclocephalini supported Dyscinetus as an early diverging member of the Cyclocephalini (Clark, 2011;Breeschoten et al, 2013). In that analysis, Cyclocephala consisted of two sub-clades, one of which included two species of Mimeoma as apical members of 'Cyclocephala sub-clade 1' (Clark, 2011).…”
Section: Taxa Selectionmentioning
confidence: 99%